Information Services with Problem Based Learning Method to Reduce Academic Stress - Devit Prawingga; A Muri Yusuf; Neviyarni Neviyarni (Global Econedu, 2019)
Academic stress is a major problem faced by students. This study aims to examine the effectiveness of information services using the problem based learning (PBL) method to reduce student academic stress. This study used a pre-experimental approach with the design of one group pretest-posttest design. The sample in this study were 20 students taken by purposive sampling technique. The instrument uses an academic stress scale developed from Aldwin's theory by measuring physical, emotional and behavioral symptoms. Analysis techniques using the Wilcoxon Signed Ranks Test. The results showed that information services with the PBL method were effective in reducing student academic stress. This can be seen from the decrease in posttest scores that occurred in all students who were given information services using the PBL method.